Einstein, relativity, and absolute simultaneity [ - Craig, William Lane; Smith, Quentin , 1952- (Routledge, 2008)
Presenting a collection of original essays from a team of international philosophers and physicists, this volume reassesses the contemporary paradigm of the relativistic concept of time. There is no other book like this currently available.